Biomimetic peptide coacervates for intracellular delivery and release of biomacromolecules - Sun, Yue (Nanyang Technological University, 2022)
Self-coacervating peptides (HBpep) derived from histidine-rich Humboldt squid beak proteins (HBPs) are considered a promising delivery platform for biomacromolecular therapeutics due to their simplicity of fabrication in full-aqueous conditions, high encapsulation efficiency, and low toxicity. Previous studies showed that biomimetic peptide coacervate microdroplets formed by HBpep are highly stable after crossing the cell membrane, but were unable to release the cargo into the cytoplasm, which has so far limited the application of this novel delivery platform. To solve this problem, in this thesis HBpep coacervates were chemically modified to confer them with stimuli-responsivity, for the goal to achieve controllable biomacromolecules delivery and release inside cells. The phase separation behavior of HBpep could be tuned by a single lysine (Lys) insertion along its sequence (HBpep-K). Due to electrostatic repulsion between positively-charged Lys residues, the HBpep-K could only form coacervates at a higher pH. Based on this altered phase behavior, a strategy was devised to allow for the controlled release of encapsulated therapeutics using a disulfide-based self-immolative modification on the inserted Lys residue. After the modification, HBpep-SR, which is named by the disulfide bond (S) and end group (R), could form coacervate microdroplets under near-physiological conditions. But these redox-responsive coacervates would be completely disassembled to release their payloads in the presence of reducing compounds. Once the cargo-loaded coacervates cross the cell membrane and reach the reducing environment of the cytoplasm, the designed redox-responsivity would be triggered to release biomacromolecule cargos. Applying this strategy, various functional biomacromolecules including proteins, peptides and nucleic acids were successfully recruited within the coacervate microdroplets and then delivered and released inside cells. Compared to commercially available transfection reagents, this coacervates-based system presented a better delivery efficacy for proteins and a comparable transfection efficiency for mRNAs. Critically, the HBpep-SR coacervates bypass classic endocytosis pathways to enter the cells, which enhanced the delivery efficiency and protected the cargo from acidic organelles. These results demonstrate the potential of using redox-responsive coacervate microdroplets to deliver therapeutic biomacromolecules, which remains a challenge for most drug delivery systems. Following the excellent performance of HBpep-SR, further optimizations were developed to broaden the pH range for coacervation, control the release kinetics, and introduce other types of stimuli-responsivity. The preliminary results of sequence alternation, chain architecture adjustment and change of stimuli-responsivity showed promising potential for the coacervate-based delivery system, which could be used as a universal platform to deliver all types of biomacromolecules for various therapeutic and biomedical applications.